L’Affaire Olesniak - Baptiste Coulmont (Genre, Sexualité et Société)
This article is a close reading of the documents produced at the time of the trial for “outrage aux bonnes mœurs” (obscenity) against a female concierge in the Pigalle neighborhood of Paris. Based on his reading of the case, the author attempts to describe the state of the pornographic market before its liberalization.